Migrant Workers, Grassroots Transnationalism, and Agency in Learning - Romee Lee (Adult Education Research Conference, 2006)
A new approach to the lifelong learning paradigm is required to include transnational learners. This research shows that migrant workers, who by definition belong to multiple communities, seek learning experiences to sustain and enhance capabilities as contemporary workers. This is the case for why global non-elites form transnational agency with learning priorities.
Keywords: lifelong learning; migrant workers; grassroots transnationalism